2015
DOI: 10.1016/j.schres.2015.07.037
|View full text |Cite
|
Sign up to set email alerts
|

COMT genotype and response to cognitive remediation in schizophrenia

Abstract: Background A functional polymorphism of the catechol-O-methyltransferase (COMT) gene (Val158Met) partially appears to influence cognitive performance in schizophrenia subjects and healthy controls by modulating prefrontal dopaminergic activity. This study evaluated the association of the COMT Val108/158 Met genotype with response to computerized neurocognitive remediation (CRT). Method 145 subjects with DSM-IV-TR schizophrenia or schizoaffective disorder were genotyped via saliva sampling. Subjects were eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…In a controlled study on CACR intervention in schizophrenia patients, Bosia et al (2007) found how COMT polymorphism might predict cognitive gain after 3-months follow-up, with a higher improvement in the Quality of Life Scale (QLS) in Met polymorphism after CR in comparison to Val/Val polymorphism after standard treatment. In line with these findings, a more recent study showed how COMT Val/Met and Met/Met genotype was linked to CR efficacy, with a greater improvement in three MATRICS cognitive domains—verbal learning, visual learning, and attention/vigilance—compared to Val/Val genotype (Lindenmayer et al, 2015). In contrast to these positive findings other studies did not find such a great association (or no association) between COMT Met/Met genotype and greater improvement after CR (Greenwood et al, 2011; Twamley et al, 2014).…”
Section: Resultsmentioning
confidence: 75%
See 1 more Smart Citation
“…In a controlled study on CACR intervention in schizophrenia patients, Bosia et al (2007) found how COMT polymorphism might predict cognitive gain after 3-months follow-up, with a higher improvement in the Quality of Life Scale (QLS) in Met polymorphism after CR in comparison to Val/Val polymorphism after standard treatment. In line with these findings, a more recent study showed how COMT Val/Met and Met/Met genotype was linked to CR efficacy, with a greater improvement in three MATRICS cognitive domains—verbal learning, visual learning, and attention/vigilance—compared to Val/Val genotype (Lindenmayer et al, 2015). In contrast to these positive findings other studies did not find such a great association (or no association) between COMT Met/Met genotype and greater improvement after CR (Greenwood et al, 2011; Twamley et al, 2014).…”
Section: Resultsmentioning
confidence: 75%
“…COMT gene variability has been associated with cognitive performance in schizophrenia (Diaz-Asper et al, 2008) and with CR response, although results have been equivocal (Bosia et al, 2007, 2014a; Greenwood et al, 2011; Pieramico et al, 2012; Panizzutti et al, 2013; Lindenmayer et al, 2015). In a controlled study on CACR intervention in schizophrenia patients, Bosia et al (2007) found how COMT polymorphism might predict cognitive gain after 3-months follow-up, with a higher improvement in the Quality of Life Scale (QLS) in Met polymorphism after CR in comparison to Val/Val polymorphism after standard treatment.…”
Section: Resultsmentioning
confidence: 99%
“…The potential of these drugs to improve executive cognitive function by selectively increasing dopamine load in the frontal cortex but not in subcortical territories, and the possibility that response to them may be modified by a COMT polymorphism, provides a novel genotype-based targeted pharmacological approach without abuse potential for the treatment of cognitive disorder in schizophrenia and in other conditions involving prefrontal cortex dysfunction." 75 COMT genotype and response to cognitive remediation in schizophrenia http://www.ncbi.nlm.nih.gov/pubmed/26255563 76 "This study evaluated the association of the COMT Val108/158 Met genotype with response to computerized neurocognitive remediation (CRT)… The low activity Met allele (Met/Met; Val/Met) was associated with significantly greater improvements in the MATRICS domains of Verbal Learning, Visual Learning and Attention/Vigilance after CRT." 76 Catechol-O-methyltransferase val158met genotype modulates sustained attention in both the drug-free state and in response to amphetamine http://www.ncbi.nlm.nih.gov/pubmed/20414144 77 "The results of this study extend earlier findings with the COMT genotypes to additional measures of cognition, and suggest that the presence of the val allele is associated with poorer performance and greater improvement with a stimulant drug."…”
Section: Treatment Of Cognitive Deficits Associated With Schizophrenimentioning
confidence: 99%
“…75 COMT genotype and response to cognitive remediation in schizophrenia http://www.ncbi.nlm.nih.gov/pubmed/26255563 76 "This study evaluated the association of the COMT Val108/158 Met genotype with response to computerized neurocognitive remediation (CRT)… The low activity Met allele (Met/Met; Val/Met) was associated with significantly greater improvements in the MATRICS domains of Verbal Learning, Visual Learning and Attention/Vigilance after CRT." 76 Catechol-O-methyltransferase val158met genotype modulates sustained attention in both the drug-free state and in response to amphetamine http://www.ncbi.nlm.nih.gov/pubmed/20414144 77 "The results of this study extend earlier findings with the COMT genotypes to additional measures of cognition, and suggest that the presence of the val allele is associated with poorer performance and greater improvement with a stimulant drug." 77 Tolcapone improves cognition and cortical information processing in normal human subjects http://www.ncbi.nlm.nih.gov/pubmed/17063156 78 "We found significant drug effects on measures of executive function and verbal episodic memory, individuals with val/val genotypes improved, whereas individuals with met/met genotypes worsened on tolcapone."…”
Section: Treatment Of Cognitive Deficits Associated With Schizophrenimentioning
confidence: 99%
“…For example, if the expression levels of overlapping genes are inversely related, this would cause gene function deletion or mutation 13,33,34 . Several studies have revealed that the functional impairment of overlapping genes may be related to diseases or associated with malignant tumours; for instance, CBS is related to homocystinuria 35 , TR and COMT may be associated with schizophrenia 36 and CHEK2 may be involved in osteosarcoma 33 . However, the current study examined only the structures and associations of expression levels of overlapping genes, which limits the understanding of overlapping gene outcomes in humans.…”
Section: Discussionmentioning
confidence: 99%